Slow control and monitoring system at the JSNS2. (21st April 2021) - Park, J S; Ajimura, S; Botran, M; Choi, J H; Choi, J W; Cheoun, M K; Dodo, T; Furuta, H; Goh, J; Harada, M; Hasegawa, S; Hino, Y; et al.
Abstract: The Sterile Neutrino Search at the J-PARC Spallation Neutron Source (JSNS^2 ) experiment aims to search for sterile neutrino oscillations using a neutrino beam from muon decays at rest. The JSNS^2 detector contains 17 tons of 0.1% gadolinium (Gd) loaded liquid scintillator (LS) as a neutrino target. Detector construction was completed in the spring of 2020. A slow control and monitoring system (SCMS) was implemented for reliable control and quick monitoring of the detector operational status and environmental conditions. It issues an alarm if any of the monitored parameters exceed a preset acceptable range. The SCMS monitors the high voltage of the photomultiplier tubes, the LS level in the detector, possible LS overflow and leakage, the temperature and air pressure in the detector, the humidity of the experimental hall, and the LS flow rate during filling and extraction. An initial 10 days of data-taking with a neutrino beam was done following a successful commissioning of the detector and SCMS in 2020 June. In this paper, we present a description of the assembly and installation of the SCMS and its performance.